Analysis of the state and trends of unemployment and ways to overcome it in Ukraine - Бабич, С. М.; Левицька, М. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
This article focuses on determining causes and factors, which shape the unemployment rate in Ukraine, and the statistical analysis of the regional section. Each state has its own peculiarities of the formation of the labor market, which are caused by resource, geographical, economic-political and other conditions. Under the influence of these features, certain trends are formed, which are traced in the period. According to the results, the dynamics of the regional unemployment rate is proved to be heterogeneous, and such heterogeneity is caused by a number of factors. The investigations led to the conclusion that the main causes of this imbalance are structural disproportions in the national economy, the lack of a mechanism for sustainable business development and stimulation of creating new working places. It is determined that the dynamics of the number of additional jobs in individual regions is positive, but the total number of additional jobs is decreasing each year, and the forecast line shows that, unfortunately, there will be a reduction in the number of new working places in Ukraine in the coming years. Following the results of the analysis, the main directions of improving the regulation of unemployment in Ukraine by extending the state’s activities on increasing and stimulating production are proposed. It is also proved that unemployment rate reduction will be achieved through a series of measures, including optimizing the labour market regulation mechanism by improving the quality of the workforce, which means increasing the level of general education and advanced training, obtaining the skills required. The mechanism encouraging investment and development of entrepreneurial activity plays an important role in the system of employment regulation measures which will generate new and additional employment opportunities.